Digital Ethnography Study on Converse Shoe Enthusiast Groups on Social Media Networks - Januar Eko Priyanto; Ratna Komala (Green Publisher Indonesia, 2024)
The purpose of this research is to obtain an overview of the communication and interaction patterns occurring within the Converse fan group, Converse Head Indonesia, using the critical-constructivism paradigm. This study employs a digital ethnography strategy with a qualitative approach, utilizing in-depth interviews and observations of the group's activities on their Facebook fan page. Through interviews with six informants selected purposively and using the snowball technique, it was found that social interactions among CHI members are grouped into nine dimensional categories based on interview questions. The results reveal that members join the network to socialize and gain access to the latest Converse products, including benefits, price information, and where to obtain them. From the interactions among CHI members, exclusivity, value standards, appearance standards, and ethics were also identified. Lastly, it was found that the interactions within the CHI group predominantly emphasize economic values.